Aspects of the sustainability of the wild honeybush industry - McGregor, Gillian Kathleen (Rhodes University, Faculty of Science, Department of Geography)
Honeybush products are uniquely South African, derived from plants of the fynbos genus, Cyclopia. Cyclopia intermedia is the most widespread species, distributed across 11 496 km2 of the Cape Fold Mountains, and provided the bulk of supply for the industry until 2022. While the industry is small, it is a locally significant industry affecting the livelihoods of harvesters, farmers and processors in the greater Langkloof region of the Eastern and Western Cape provinces of South Africa. The industry has evolved from a cottage one, to a commercial scale, and concerns have been raised over the sustainability of the wild resource specifically, and the industry in general. The research aimed to improve our understanding of aspects of the sustainability of the wild honeybush industry. A mixed methods design was adopted, which allowed for the inclusion of data collection approaches and analysis which tell a richer story than one with a singular modus. Four objectives were identified, which entailed: (i) mapping the resource to establish the distribution range of C. intermedia; (ii) recording of local ecological knowledge (LEK) and traditional ecological knowledge (TEK) around best practice harvesting; (iii) assessing the sustainability of harvest enterprise types through analysis of yield history and harvester loads; (iv) identifying differences between harvested and unharvested C. intermedia populations. Mapping of the resource drew on a variety of existing data sources, field mapping, GIS-based analysis, species distribution modelling and expert mapping to create a comprehensive and accurate map of the species distribution. The species is estimated to occupy a distribution range of 11 496 km2, 49% of which occurs in formally protected areas. Based on local scale mapping by experts, 100km2 is estimated to be in use for wild harvesting in the production area of the Langkloof. Information on best practice harvesting was collected through in-depth interviews with harvesters, harvest managers, processors and farmers (in the field at harvest events) and through questionnaire surveys and focus group discussions at a honeybush stakeholder workshop. In combination with harvest event surveys at which harvester practice was observed and recorded, and surveys were conducted of the harvest yield and of plants in the harvested population, the information was used to produce the first formal account of best practice for sustainable harvesting of wild honeybush. To assess the sustainability of harvest enterprises and associated harvester livelihoods, harvester managers were interviewed to create profiles of typical harvesting enterprises based on their practices and harvest yield histories. Of the three harvest enterprises considered, two showed sustained yields over time, while those of a large contract type enterprise were less sustainable with declining yields on three out of six farms. From a statistical analysis of the records it was found that the most effective team size was 10 or less harvesters in terms of livelihood sustainability. They could earn a fair livelihood (ZAR67 680.00) per annum, based on a 94 kg load per daily harvest event, sold to the processor at ZAR 5.00, for nine months of the year, working a four-day week. For a team to operate sustainably, it was found that it should consist of experienced harvesters harvesting conservatively, at intervals of at least four years, and be responsive to local environmental conditions. Detailed field surveys of C. intermedia plants at 38 sites representing harvested and unharvested populations were carried out to understand the impact of harvesting on the plants. A statistical analysis of the plant's dimensions related to the physical environment, fire and harvest history using generalised linear models revealed that while unharvested plants were slightly larger, only crown diameter and stem counts were significantly so. Seedlings were noticeably scarce at all sites, including recently burnt sites. A significant finding of the research was that in a fecundity survey, unharvested plants produced significantly more pods. The impact of this is unknown, but it has implications for management and the sustainable use of wild resources in the long term. Further understanding of the impact of harvesting came from surveys of cultivated stands of C. intermedia (different ages and harvest histories, but all harvested at three-year intervals) and surveys of a wild population, which was subjected to unregulated harvesting. For the cultivated stand: after 12 years, plants declined in all measured dimensions, while in the wild population, 45% of the plants died over a seven-year period. The surveys proved that a three-year interval or frequent, unregulated harvest is unsustainable. The research was used to produce the wild harvesting guidelines, which have become the accepted standard for the industry. It has demonstrated that under the right circumstances, harvesting of the wild C. intermedia resource is broadly sustainable. However, there needs to be informed management of the use of the resource in terms of harvest team types and their protocols, particularly with regard to harvest intervals and possible interventions to improve seed production to achieve sustainable use of the resource in social, economic and ecological terms.
Keywords: Cyclopia intermedia; Renewable natural resources -- South Africa; Sustainability; Local ecological knowledge; Harvesting